Maternal Risk factors, morbidity, and mortality pattern of LBW babies admitted in NICU: A Retrospective study done in Banas Medical College and Research Centre, Palanpur, Gujarat, India - Sharma, Dr. Neha; Dr. Ajit K. Shrivastava; Dr. Santosh K. Roy; Dr. Heenaben R. Desai; Dr. Anjum A. Hasan (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: This study was undertaken to know about the maternal risk factors, morbidity, and mortality of low birth weight (LBW) babies admitted to NICU in a tertiary care hospital. Methods: This is a hospital-based, retrospective, descriptive study, done on LBW babies admitted to the NICU of Banas Medical College and Research Institute, Palanpur from January 2019- March 2020. Results: Out of the 1018 newborns admitted to NICU, 735 were LBW babies and 700 LBW babies were analyzed because 35 cases did not fit in inclusion criteria. The magnitude of LBW babies was 68.7 %.Out of 700 LBW babies, 530 (75.7%) had weight between 1.5kg to 2.49 kg,138 (19.7%) babies were of VLBW ( 1kg -1.5kg) and 32(4.57%) babies were of ELBW (weight <1 kg).Out of 700 LBW babies, 450 (64.3%)were males and 250(35.7%) were females and 60 (8.57%) were term babies and 640 (91.42%)were preterm babies. Among the maternal risk factors most common was maternal undernutrition (30%), followed by maternal anemia in 180 cases (25.7%), inadequate ANC visits in 170 cases (24.2%), maternal age <20 years in 110 cases (15.7%). Less common causes were bad obstetric history (1.14%), Twins delivery (1%), acute infections, and elderly primi (0.85%) respectively and the least common was PROM in 0.42%. Out of 700 babies, morbidity was seen in 590 LBW babies (84.28%). Conclusion: Identification of maternal risk factors and providing proper care and appropriate management to LBW can reduce neonatal morbidity and mortality